2002
DOI: 10.1002/jso.10170
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in patients with transitional bladder cancer

Abstract: Although a wider study is necessary, our results suggest that the enhanced NO levels could perhaps be considered as a putative marker in TBC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(29 reference statements)
2
14
0
Order By: Relevance
“…It has been reported that continuous NO production may be involved in the inflammatory process associated with the appearance of many human malignancies, including bladder cancer (O’Byrne and Dalgleish 2001). Furthermore, it has been reported that NO is elevated in the urine from patients with bladder cancer (Eijan et al 2002). However, Bukan et al (2003) did not observed any significant difference in serum total nitrite levels of the patients with bladder cancer and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that continuous NO production may be involved in the inflammatory process associated with the appearance of many human malignancies, including bladder cancer (O’Byrne and Dalgleish 2001). Furthermore, it has been reported that NO is elevated in the urine from patients with bladder cancer (Eijan et al 2002). However, Bukan et al (2003) did not observed any significant difference in serum total nitrite levels of the patients with bladder cancer and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Various lines of evidence reported an increased oxidative stress in patients with breast cancer [152,153]. Increased NO levels have been reported in bladder cancer patients [154]. This NO stimulates matrix metalloproteinases (MMPs), especially prolidase activity, which is involved in the terminal step of collagen degradation.…”
Section: Bladder Cancermentioning
confidence: 99%
“…An inverse correlation has been defined between NOS presence and tumor differentiation in human gynecologic tumors and human colorectal carcinoma cells 11,19 . Such a correlation was not observed between urine or tumor tissue NO and iNOS expression with tumor grade or stage 13,15 , 17 . Results of the present study were also in accordance with current literature.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the association of NO with bladder cancer has been investigated by demonstrating iNOS expression in cancer tissue immunohistochemically, but quantitative measurement of serum, urine or tissue NO has rarely been performed 15–17 . Because iNOS expression was recently shown in bladder cancer tissue, Eijan et al .…”
Section: Discussionmentioning
confidence: 99%